Correlation Between Mobile Legends Playing Intensity and Vocabulary Development Among Senior High School Students - Andika Rosadi Siraje; Darmawan; Budi; Mochtar Marhum (MASI Mandiri Edukasi, 2025)
This study investigates the correlation between the intensity of playing Mobile Legends and vocabulary development among senior high school students. The growing adoption of digital games for educational purposes—particularly in language learning—necessitates research into their integration within structured learning environments. Utilizing a quantitative correlational design, the study involved 25 purposively selected students from SMA Labschool Untad Palu who actively participated in a Mobile Legends extracurricular program. Data were collected through a 15-item Likert-scale questionnaire measuring gameplay intensity and a 30-item vocabulary test targeting common nouns, verbs, and adjectives derived from gameplay contexts. The questionnaire demonstrated strong internal consistency (Cronbach's Alpha = 0.882), and all items were deemed valid. Results from the Pearson Product-Moment correlation analysis indicated a moderate, statistically significant relationship between gameplay intensity and vocabulary acquisition (r = 0.538, p = 0.005). These findings suggest that structured digital gameplay in English-language environments can support incidental vocabulary learning and serve as an effective pedagogical supplement to conventional instruction.